The Dominant Role of Extreme Precipitation Events in Antarctic Snowfall Variability. Issue 6 (22nd March 2019) - Turner, John; Phillips, Tony; Thamban, Meloth; Rahaman, Waliur; Marshall, Gareth J.; Wille, Jonathan D.; Favier, Vincent; Winton, V. Holly L.; Thomas, Elizabeth; Wang, Zaomin; van den Broeke, Michiel; Hosking, J. Scott; et al.
Abstract: Antarctic snowfall consists of frequent clear‐sky precipitation and heavier falls from intrusions of maritime airmasses associated with amplified planetary waves. We investigate the importance of different precipitation events using the output of the RACMO2 model. Extreme precipitation events consisting of the largest 10% of daily totals are shown to contribute more than 40% of the total annual precipitation across much of the continent, with some areas receiving in excess of 60% of the total from these events. The greatest contribution of extreme precipitation events to the annual total is in the coastal areas and especially on the ice shelves, with the Amery Ice Shelf receiving 50% of its annual precipitation in less than the 10 days of heaviest precipitation. For the continent as a whole, 70% of the variance of the annual precipitation is explained by variability in precipitation from extreme precipitation events, with this figure rising to over 90% in some areas. Plain Language Summary: The Antarctic ice sheet is extremely important because of its possible contribution to sea level rise and through the climate records than can be reconstructed using chemical signals locked in the ice. The mass of the ice sheet is constantly changing because of the ice gained by snowfall and the loss of ice at the margins via iceberg calving and melt through contact with relatively warm water masses. The amount of snow falling on the Antarctic is highly variable and dependent on the meteorological conditions over the Southern Ocean and the penetration of marine air into the interior. We show that extreme snowfall events, defined at the heaviest 10% of daily precipitation amounts, contribute a high percentage of the annual snowfall and are the main factor controlling the year‐to‐year variability of snowfall across the continent. This has implications for the reconstruction of past climate records using data from ice cores and the selection of future ice core drilling sites. Key Points: Extreme precipitation events explain 70% of the interannual variance of Antarctic snowfall Extreme precipitation events are particularly important over western West Antarctica and on the Ross and Amery Ice Shelves Tropical climate variability is important in modulating the frequency of extreme precipitation events in the West Antarctic sector